Moving Through the Literature: What Is the Emotion Often Denoted Being Moved?. (April 2019) - Zickfeld, Janis H.; Schubert, Thomas W.; Seibt, Beate; Fiske, Alan P.
When do people say that they are moved, and does this experience constitute a unique emotion? We review theory and empirical research on being moved across psychology and philosophy. We examine feeling labels, elicitors, valence, bodily sensations, and motivations. We find that the English lexeme being moved typically (but not always) refers to a distinct and potent emotion that results in social bonding; often includes tears, piloerection, chills, or a warm feeling in the chest; and is often described as pleasurable, though sometimes as a mixed emotion. While we conclude that it is a distinct emotion, we also recommend studying it in a more comprehensive emotion framework, instead of using the ambiguous vernacular term being moved as a scientific term.